2019
DOI: 10.1111/cas.14205
|View full text |Cite
|
Sign up to set email alerts
|

Pimozide suppresses cancer cell migration and tumor metastasis through binding to ARPC2, a subunit of the Arp2/3 complex

Abstract: ARPC2 is a subunit of the Arp2/3 complex, which is essential for lamellipodia, invadopodia and filopodia, and ARPC2 has been identified as a migrastatic target molecule. To identify ARPC2 inhibitors, we generated an ARPC2 knockout DLD‐1 human colon cancer cell line using the clustered regularly interspaced short palindromic repeats/CRISPR‐associated protein 9 (CRISPR/Cas9) system and explored gene signature‐based strategies, such as a connectivity map (CMap) using the gene expression profiling data of ARPC2 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Through a Connectivity Map (CMap)-based drug discovery strategy as a new screening method, Choi and co-workers identified pimozide, an antipsychotic drug used in the clinic, as an ARPC2 inhibitor [374]. This compound has been shown to strongly impair migrating and invasive abilities of different cancer cells.…”
Section: And N-wasp and Arp2/3 Complex And Formin Inhibitorsmentioning
confidence: 99%
“…Through a Connectivity Map (CMap)-based drug discovery strategy as a new screening method, Choi and co-workers identified pimozide, an antipsychotic drug used in the clinic, as an ARPC2 inhibitor [374]. This compound has been shown to strongly impair migrating and invasive abilities of different cancer cells.…”
Section: And N-wasp and Arp2/3 Complex And Formin Inhibitorsmentioning
confidence: 99%
“…Pimozide is an antagonist for dopamine receptors; it is employed to treat Gilles de la Tourette syndrome and schizophrenia ( 84 ). Additionally, pimozide has shown promising results for managing several cancers, including skin cancer ( 36 , 85 87 ). An early clinical trial showed that pimozide might have beneficial effects in patients with formerly medicated metastatic melanoma ( 86 ).…”
Section: Drug Repurposing For Skin Cancermentioning
confidence: 99%
“…An early clinical trial showed that pimozide might have beneficial effects in patients with formerly medicated metastatic melanoma ( 86 ). The possible molecular mechanism for this anti-metastatic effect could be mediated by inhibition of ARPC2, a subunit of the Arp2/3 complex involved in migration and invasion ( 85 ). Moreover, preclinical studies demonstrated that the combination of pimozide with other drugs might enhance its anti-melanoma activity.…”
Section: Drug Repurposing For Skin Cancermentioning
confidence: 99%
“…Inhibition of the Arp2/3 complex in glioblastoma cells resulted in the loss of cell lamellipodia and polarity, which was associated with reduced migration and invasion [ 57 ]. Furthermore, Choi et al presented the possibility of limiting the migration and invasion of cancer cells (lung, pancreas, and colon) by blocking the function of ARPC2 using pimozide [ 104 ].…”
Section: The Involvement Of Actin and Abps In Cancer Progression (mentioning
confidence: 99%